An international cohort study of birth outcomes associated with hospitalized acute respiratory infection during pregnancy. Issue 1 (July 2020) - Regan, Annette K.; Feldman, Becca S.; Azziz-Baumgartner, Eduardo; Naleway, Allison L.; Williams, Jennifer; Wyant, Brandy E.; Simmonds, Kim; Effler, Paul V.; Booth, Stephanie; Ball, Sarah W.; Katz, Mark A.; Fink, Rebecca V.; et al.
Highlights: Severe pandemic influenza infection in pregnancy can adversely impact fetal health. Fewer studies have evaluated seasonal influenza and non-influenza infections. Hospitalized influenza and non-influenza infections increased risk of preterm birth. Preventing maternal seasonal respiratory infections may have fetal health benefits. Abstract: Objectives: Findings during the 2009 pandemic suggest severe maternal infection with pandemic influenza had adverse perinatal health consequences. Limited data exist evaluating the perinatal health effects of severe seasonal influenza and non-influenza infections during pregnancy. Methods: A retrospective cohort of pregnant women from Australia, Canada, Israel, and the United States was established using birth records to identify pregnancies and birth outcomes and hospital and laboratory testing records to identify influenza and non-influenza associated acute respiratory or febrile illness (ARFI) hospitalizations. ARFI hospitalized women were matched to non-hospitalized women (1:4) by country and season of conception. Log-binomial regression was used to estimate the relative risk (aRR) of preterm birth (PTB), small-for-gestational-age (SGA), and low birthweight (LBW) birth, adjusting for pre-existing medical conditions, maternal age, and parity. Results: 950 pregnant women hospitalized with an ARFI were matched with 3, 800 non-hospitalized pregnant women. Compared to non-hospitalized women, risk of PTB was greater among women hospitalized with influenza-associated ARFI (aRR: 1.57; 95% CI: 1.15–2.15) and non-influenza ARFI (aRR: 2.78; 95% CI: 2.12–3.65). Similar results were observed for LBW; there were no associations with SGA birth. Conclusions: ARFI hospitalization during pregnancy was associated with increased risk of PTB and LBW.